2014
DOI: 10.1021/jo501141y
|View full text |Cite
|
Sign up to set email alerts
|

Selective Reduction of Aromatic Ketones in Aqueous Medium Mediated by Ti(III)/Mn: A Revised Mechanism

Abstract: An experimental study on the role played by each of the reagents involved in the selective reduction of aromatic ketones in aqueous medium is reported. In this reaction, the reduction of aromatic ketones is mediated by Cp2TiCl. Moreover, the presence of Mn in the reaction medium is mandatory. To account for these findings, a substantially revised mechanism is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…Cp 2 TiCl‐mediated pinacolisation of aromatic and α,β‐unsaturated aldehydes was reported as an inner‐sphere electron transfer generating the corresponding titanoxy radicals 37–40. However, the free‐radical character conventionally assumed for these chemical processes should be reconsidered on the basis of a study by Rosales and Oltra et al41 These authors reported a detailed experimental study of the role played by each of the reagents involved in the homocoupling and in the selective reduction of aromatic ketones in aqueous medium, promoted by Cp 2 TiCl/Mn. It was observed that Mn is required not only for the reduction of Cp 2 Ti IV Cl 2 to Cp 2 Ti III Cl, but also for the irreversible generation of a titanaoxirane 6 , which, under anhydrous conditions is transformed into pinacol coupling products (Scheme ).…”
Section: Principal Transformations Mediated By the Nugent Reagentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cp 2 TiCl‐mediated pinacolisation of aromatic and α,β‐unsaturated aldehydes was reported as an inner‐sphere electron transfer generating the corresponding titanoxy radicals 37–40. However, the free‐radical character conventionally assumed for these chemical processes should be reconsidered on the basis of a study by Rosales and Oltra et al41 These authors reported a detailed experimental study of the role played by each of the reagents involved in the homocoupling and in the selective reduction of aromatic ketones in aqueous medium, promoted by Cp 2 TiCl/Mn. It was observed that Mn is required not only for the reduction of Cp 2 Ti IV Cl 2 to Cp 2 Ti III Cl, but also for the irreversible generation of a titanaoxirane 6 , which, under anhydrous conditions is transformed into pinacol coupling products (Scheme ).…”
Section: Principal Transformations Mediated By the Nugent Reagentmentioning
confidence: 99%
“…Recently, an experimental study on the role played by each of the reagents involved in the selective reduction of aromatic ketones in aqueous medium has been reported by Rosales, Oltra et al41 In that study, the authors reported that the reduction of aromatic ketones is mediated by Cp 2 TiCl and that the presence of Mn in the reaction medium is mandatory. It was proposed that coordination between acetophenone and Cp 2 TiCl provided the intermediate 10 in an equilibrium reaction shifted towards Cp 2 TiCl and acetophenone, because in the absence of Mn, acetophenone was recovered unchanged.…”
Section: Principal Transformations Mediated By the Nugent Reagentmentioning
confidence: 99%
“…This SET is capable of promoting and/or catalyzing several transformations in organic chemistry [ 17 25 ]. One of the most relevant transformations is the H/D-atom transfer from H 2 O/D 2 O to carbon radicals (pathway A) (obtained from epoxides [ 26 28 ], ozonides [ 29 ] or activated halides [ 30 ] and Cp 2 TiCl/Mn), to intermediate titanaoxiranes (pathway B) [ 31 32 ] (obtained from carbonyl compounds and Cp 2 TiCl/Mn), and to late transition metals (pathway C) [ 33 ] in a process mediated by Cp 2 TiCl/Mn/H 2 O or D 2 O which allows for the reduction of alkenes or alkynes ( Scheme 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In any case, apart from mechanistic considerations, the Cp 2 TiCl/D 2 O/Mn mixture has emerged as an excellent reagent for the deuteration of organic compounds from epoxides [ 2 , 27 , 37 ], ozonides [ 29 ], ketones [ 31 32 ], activated halides [ 30 32 ], alkenes and alkynes [ 33 ]. Several examples are presented in Scheme 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Although pinacolizations mediated by Ti(III) species of aldehydes have been reported utilizing dimeric Ti(III) species (see Section 8.2), the stereoselective pinacol couplings of unsaturated ketones was achieved via a titanaoxirane intermediate 48 using a stoichiometric amount of Cp 2 TiCl 2 and a large excess of Mn (see Scheme 28). 50,51 The homocoupling of aromatic ketones proceeded in good yield with a high dl stereoselectivity whereas lower yields and stereoselectivity were obtained with α,β-unsaturated ketones. 50 The formation of the corresponding lactones in good yield was also observed through the heterocoupling of acetophenone with a large excess of methyl acrylate or crotonate.…”
Section: Pinacol Coupling Of Ketonesmentioning
confidence: 99%